Validation Of A Scoring System For Difficult Laparoscopic Cholecystectomy Prediction :Pilot Study - Irum Masood; Ahmed Raheem (ziauddin University, 2024)
Background: Laparoscopic cholecystectomy is excellence of care for the dealing of indicative disease of the gallbladder and commonly repeated operation being carried out by the surgeons. Occasionally done straightforwardly and rapidly and sometimes hard and prolonged. Guess of the situation involving exposure to danger of complication to turning or pitfall of surgery is a key angle for surgeons to setting up of surgery accordingly. But there is no handy scoring tool. The point at a target of our pilot survey is to analyze the feasibility of conducting a large study to validate a scoring tool developed at our institution. Methods: Eleven patients included, study conducted in general surgery department, Ziauddin University and hospitals. Patient's assessment and surgery done by four experienced Surgeons. The variables such as up in years especially in male sex, past events of cholecystitis, pancreatitis, Overweight, past surgery on abdomen, noticeable gallbladder, gallbladder status and wall thickness, CBD diameter hematological/biochemical appraise in scoring method. Results: We found that history of cholecystitis/pancreatitis, Significant variables were status and density of the gallbladder for the guess of tough laparoscopic cholecystectomy. P Values of scoring tool were p 0.001 for easy and p 0.001 for difficult case. The turning figure was 1(14.3%) and p 0.388 from conventional to open cholecystectomy. Conclusion: This preoperative prediction scoring system is accurate, feasible, and inexpensive tool for use in selected clinical trials of gallstone disease. Further studies with large sample size and validation of this new method for assessment of treatment response are warranted. Key Words: Laparoscopic cholecystectomy, validation study, Pilot study, scoring system